Periodontal effect of augmented corticotomy-assisted orthodontics versus conventional orthodontics in treatment of adult patients with bialveolar protrusion - Bing Wang; WenQiong Xi; Hui Chen; Jinlong Shao; Aimei Song; Fan Zhang (BMC, 2022)
Abstract Background The patients of bialveolar protrusion always demonstrate thin anterior alveoli which may aggravate subsequent gingival recession and bone loss during retraction. This study aimed to investigate the periodontal changes, including alveolar height, thickness, and area, and the width of keratinized gingiva, in mandibular anterior teeth after augmented corticotomy-assisted orthodontics (ACAO) compared with traditional orthodontics. Methods Twenty adult patients with skeletal class I bialveolar protrusion were selected from two groups: ACAO group (augmented corticotomy on the labial side of the anterior mandibular teeth, n = 10) and control group (conventional orthodontics, n = 10). In all patients, four first premolars were extracted and the incisors were retracted under the maximum anchorage. The measurements included the labial alveolar bone area, vertical alveolar bone height, alveolar bone thickness surrounding the mandibular anterior teeth, root length, gingival recession and width of keratinized gingiva after alignment (T0) and 3 months after space closure (T1). Results The labial alveolar height, area, and thicknesses all decreased after space closure in the control group but significantly increased in the ACAO group. The decrease in the lingual alveolar height was statistically less in the ACAO group than that in the control group. Besides, the width of keratinized gingiva increased in the ACAO group but decreased in the control group. There was no significant difference in the changes of root length between groups. The dentoalveolar changes between anterior teeth were consistent but with different scales. The lateral incisors gained the most labial bone height and area. Conclusion Compared to conventional orthodontics, ACAO provided a more favorable effect of improving periodontal status surrounding the mandibular anterior teeth for Class I maxillary protrusion patients.